2014
DOI: 10.14236/jhi.v21i1.61
|View full text |Cite
|
Sign up to set email alerts
|

Getting on with your computer is associated with job satisfaction in primary care: entrants to primary care should be assessed for their competency with electronic patient record systems

Abstract: Job satisfaction in primary care is associated with getting on with your computer. Many primary care professionals spend longer interacting with their computer than anything else in their day. However, the computer often makes demands rather than be an aid or supporter that has learned its user's preferences. The use of electronic patient record (EPR) systems is underrepresented in the assessment of entrants to primary care, and in definitions of the core competencies of a family physician/general practitioner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Moreover, previous research has concluded that the development of health care professionals' digital health competence requires systematic and individually‐designed education (Nazeha et al, 2020). Additionally, organisational and collegial support (Jimenez et al, 2020; Konttila et al, 2018), and patient‐friendly designs, are a starting point for the efficient use of ICT solutions by health care professionals (Lusigan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous research has concluded that the development of health care professionals' digital health competence requires systematic and individually‐designed education (Nazeha et al, 2020). Additionally, organisational and collegial support (Jimenez et al, 2020; Konttila et al, 2018), and patient‐friendly designs, are a starting point for the efficient use of ICT solutions by health care professionals (Lusigan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…8 Some authors express concern that the presence of the EHR and the related demands of documentation may decrease clinicians' satisfaction with their work. 9 Other studies suggest that despite early clinician fears about the negative effects of an EHR, these dissipated after implementation and clinicians found that the EHR facilitated patient engagement and education. 10 Early qualitative research on EHR implementation described the changes in clinical communication introduced into a visit with the EHR.…”
Section: Introductionmentioning
confidence: 99%